Factors influencing the choice of private or public schools: Evidence from Georgia - Tarkhnishvili, Anna; Tarkhnishvili, Levan; Strielkowski, Wadim (Frontiers in Education, 2022)
The existence and development of public schools is influenced by a plethora of factors. Through the creation of education policies, any state education system is striving to accomplish specific goals. Both informal and formal private schooling is taking the lead in all cultures and societies. Unmistakably, the distinction between private and public schools is evident. However, given the different circumstances, choosing the best alternative for a child is regularly a fervently discussed topic among parents. There is no universal answer to the question whether private schools are actually better than or superior to the public schools. Our research aimed to describe the school choice process, it focuses on unveiling the factors and their interrelation while the parent choosing between two types of schools – private and public. The key questions for the research were as follows: 1) How interested the parents are to be actively involved in school choice process and spend certain period of time for that? 2) What factors are considered by the parents during school choice and what is the source they receive information from? 3) Does the family’s socioeconomic condition and the kids gender have influence on the process? It’s worth mentioning that, generally the research results fully coincide with the school choice theory arguments and the research findings conducted in the similar field. All these are described and presented in the first part of the article. The probabilities listed on the base of the current data, that the information source, the parent’s information level, the parents’ engagement as well as the family’s socioeconomic and demographic status play integral role in the school choice process appeared to be genuine. Apparently, the parents are much interested to provide perfect future for their kids, though socioeconomic conditions, environment, poor educational system limits their choice. Once our results compared to the existing literature and theory, one can see that our study conducted in Georgia follows the trends of the developed countries, known as the “Heyneman-Loxley effect”.